2022
DOI: 10.3390/agriculture12040568
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Farming System on Potato Yield and Tuber Quality in Northern Baltic Sea Climate Conditions

Abstract: For finding more sustainable cropping systems, this study on how the farming system influences the yield and quality of potato tubers was carried out with long-term crop rotation experiment. The long-term five-field crop rotation field trial was established with the following farming system treatments: organic farming system treatments: Org I (organic control), Org II (organic crop rotation with winter cover crops) and Org III (organic crop rotation with winter cover crops and the addition of composted cattle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This indicates that biological properties developed over time to reduce disease severity, potentially due to changes in soil microbial characteristics, general suppression, or other biological mechanisms. Other research has indicated the effects of compost and organic matter amendments on soil microbiology and soil microbial communities [41,51], as well as significant effects on soilborne diseases [52], and organic amendments have been noted for their role in shaping soil microbial communities and the development of disease-suppressive soils [53,54]. However, some short-term studies have not shown significant effects on soilborne diseases or potato yield with various compost amendments [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that biological properties developed over time to reduce disease severity, potentially due to changes in soil microbial characteristics, general suppression, or other biological mechanisms. Other research has indicated the effects of compost and organic matter amendments on soil microbiology and soil microbial communities [41,51], as well as significant effects on soilborne diseases [52], and organic amendments have been noted for their role in shaping soil microbial communities and the development of disease-suppressive soils [53,54]. However, some short-term studies have not shown significant effects on soilborne diseases or potato yield with various compost amendments [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Organic farming has less negative impact on the environment than conventional farming based on chemical fertilizers [21].The long use of mineral fertilizers has caused irreparable damage to soil structures, mineral cycles, soil microbial flora, and plants [22][23][24]. Intensified N fertilization decreased the content of dry matter and starch in potato tubers [25,26]. At the same time, excessive fertilizer usage leads to the waste of resources, reduction of biodiversity, and environmental pollution [27][28][29], which restricts agricultural production.…”
Section: Introductionmentioning
confidence: 99%
“…One of the species whose share in organic farming is small is the potato. This is due to the difficulties in growing this crop in organic production systems, mainly with regard to protection against pathogens such as Phytophthora infestans and Colorado potato beetle (Leptinotarsa decelminatea) [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%